Int Adv Otol 2021
DOI: 10.5152/iao.2021.9072
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the Half Somersault Maneuver in Comparison to the Epley Maneuver in Patients with Benign Paroxysmal Positional Vertigo

Abstract: OBJECTIVE: Benign Paroxysmal Positional Vertigo (BPPV) as the most common vestibular disorder can affect the quality of life. This study aimed to compare the effectiveness of the half somersault maneuver (HSM) as a treatment to that of the Epley maneuver (EM) as a clinical-based treatment in subjects with PC-BPPV. Methods: In this randomized study, 43 participants with unilateral posterior canal BPPV were recruited. The experimental group received the HSM, whereas the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The total of 8 sessions were held (twice a day, 2 days a week, for 2 weeks). (10) First assessment was at baseline, and the second assessment was done after two weeks. SPSS version 22 was used for data analysis.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The total of 8 sessions were held (twice a day, 2 days a week, for 2 weeks). (10) First assessment was at baseline, and the second assessment was done after two weeks. SPSS version 22 was used for data analysis.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Khaftari MD et al, verified the efficacy of the Epley maneuver in the management of BPPV, as shown in the current investigation. Exercises like the "Half somersault" have been suggested as an alternative to the Epley that is more resistive but also has less risks 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatments (vestibular suppressants) for BPPV that work when individuals report continuing to have symptoms after a successful Epley's maneuvers. Many explanations have been proposed for these persistent signs and symptoms 20 . According to Knoll RM et al, those who have persistent symptoms often experience psychological distress or dread of more episodes of dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…19,24 Another item is the VRBQ, which is a specific scale designed specifically to treat patients receiving vestibular rehabilitation that can better evaluate the efficacy of vestibular rehabilitation and changes in quality of life. 20,25 There are tens of special assessment scales for patients with vestibular dysfunction thus far, but most of them focus on quantifying the severity of vertigo symptoms and lack the assessment of the quality of life dimension. 26 Moreover, these scales do not involve reactivity tests, and the availability of clinical efficacy evaluations needs to be discussed.…”
Section: Discussionmentioning
confidence: 99%